PRODUKTIVITAS TRAKTOR CATERPILLAR D7G DI SUATU PERUSAHAAN HAK PENGUSAHAAN HUTAN DI JAMBI - Dulsalam Dulsalam; Sukanda Sukanda (Jurnal Penelitian Hasil Hutan, 1989)
An  investigation   on  the  productivity  of  D7G  Caterpillar  tractors  was carried out  at a  forest  company   in Jambi  in 1985.   Three  tractors  were  selected   randomly   to  be  observed.   The productivity  of  these  tractors  was collected   through work   time  study.   The  purpose   is  to  find   the productivities   of  D7G  Caterpillar  tractors  so  that this  information   can  be used  by  forest  companies   in planning  skidding  operations.   This  investigation   results  reveal  that  : 1.  D7G  Caterpillar  tractors  can be used to skid  logs at dryland  forests  having easy and moderate topographies.  At  skidding distances  ranuine from   75 -   535  m  with  an average of 324  m these tractors can skid  logs having volumes  ranging from 5.01 -   16.88  m3/trip   with  an average of 9.08   m3/trip.2.  The  average productivities    of  A,  B and   C skidding   tractors  were  59.22,   89.81 and 123.69   m8.   hm/hour,  respectively.The  productivities    among  tractors  were significantly   different  due  to different skidding  distances,   tractor  conditions, driver  skills,  average stund   volume  per  ha,   soil conditions,   skidded   log volume  and  topography.   The  average produc- tivity  of  the  three  tractors  was  92.09   m3 hm/hour.